Analysis of Patient Satisfaction in The Context of Health Worker Performance at The Community Health Center Ngoro District Mojokerto In 2023 - Zubaidah, Risna; Noer Saudah (Kirana Publisher (KNPub), 2023)
Human Resources are the main factor of problems that often arise in an organization such as in health service institutions. Puskesmas as a health service that is directly related to the lower community has an important role in achieving the quality of health services. the phenomenon of patient satisfaction the results of interviews with researchers at UPT Puskesmas Ngoro in July 2023 obtained data, out of 15 people, 10 still complained that they were not satisfied, and 7 were satisfied with the performance of health workers. The purpose of this study was to analyze patient satisfaction with the performance of health workers at UPT Puskesmas Ngoro in 2023. The research method used in this research is quantitative survey research (survey research). Research design in this study is quantitative research with cross sectional method. The sampling technique used accidental sampling and data analysis using the Spearman Rank statistical test. The results showed that of the 68 respondents, most (73.5%) stated that the performance of health workers was very good, namely 50 respondents. From the results of this study indicate that the level of patient satisfaction from each dimension of satisfaction ranges from 87% to 90%, which is very satisfied, meaning that patients at the puskesmas have rated well the services provided by the puskesmas. Based on the Spearman Correlation test using SPSS, the p value is 0.008 α 0.05, meaning that H0 is rejected and H1 is accepted, which can be concluded that this study shows that there is a relationship between the performance of health workers and the level of patient satisfaction at UPT Puskesmas Ngoro, Mojokerto Regency in 2023.